(untitled) (LEARNing Landscapes, 2012)
The authors facilitated three inter-professional mentorship workshops in Fiji and Tonga, which were part of a series of such events that they recently conducted across the Pacific region. These workshops, in turn, formed part of a larger, ongoing leadership initiative co-sponsored by several local, regional, and international organizations. The purpose of each workshop was to facilitate each multi-disciplinary cohort of leaders in attendance to begin to create an adaptable mentorship model that would fit their unique Pacific contexts. One task within these model-development sessions was for each cohort to create metaphors that they believed best encapsulated the essence of their specific mentorship approach. In this article, the authors summarize aspects of that creative process, present several metaphors that the three cohorts generated, and raise implications regarding future mentoring initiatives.